2013
DOI: 10.4314/tjpr.v12i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diarrhea and anti-oxidant properties of Magnolol

Abstract: Purpose: To provide an experimental basis for the anti-diarrheal and anti-oxidant properties of the bark extract of Magnolia officinalis 60.34 ± 5.17, 59.61 ± 7.66, and 54.12 ± 7.27 %, respectively, as against 70.1 ± 6.89

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 22 publications
(18 reference statements)
3
19
1
Order By: Relevance
“…5), suggesting that magnolol induce CAT activity and that could provide antioxidant protection in the cells against oxidative stress. Studies have shown that magnolol treatment increased the CAT and SOD activity in the Kunming mice [20]. Our study also suggests using yeast as a model organism to study the antioxidant property of a natural compound in vivo.…”
Section: Discussionmentioning
confidence: 63%
“…5), suggesting that magnolol induce CAT activity and that could provide antioxidant protection in the cells against oxidative stress. Studies have shown that magnolol treatment increased the CAT and SOD activity in the Kunming mice [20]. Our study also suggests using yeast as a model organism to study the antioxidant property of a natural compound in vivo.…”
Section: Discussionmentioning
confidence: 63%
“…A major bioactive constituent of the bark of Magnolia officinalis is 5,5 -diallyl-2,2 -dihydroxybiphenyl, a hydroxylated biphenyl compound called magnolol (MG) whose anti-inflammatory [4], anti-oxidative [5], anti-diabetic, anti-tumorgenic [6], anti-neurodegenerative, anti-depressant and anti-microbial [7] properties have been recently demonstrated. This compound also regulates hormones, exhibits positive gastrointestinal and uterus modulatory effects, offers cardio-vascular and liver protection and is effective in pain control [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The current studies indicate that honokiol exerts significant antidiarrheal and antimotility activity. Furthermore, our previous studies have also showed that magnolol has both antidiarrheal and antimotility effects [12]. Honokiol and magnolol are two biphenolic compounds.…”
Section: Groupmentioning
confidence: 99%
“…The remaining three groups were orally administered by gavage with the honokiol extract solution at doses of 25 (Honokiol 25), 50 (Honokiol 50) or 100 (Honokiol 100) mg honokiol/kg BW respectively at the same volume. The dose setting of honokiol in this study referred to results of Hsieh et al [10], Atanasov et al [11] and Pang et al [12].…”
Section: Castor Oil-induced Diarrheamentioning
confidence: 99%
See 1 more Smart Citation